The Effect of Botanical Pesticides on Pest Infestation Levels - Nandini Ayuningtias; Sutiharni Sutiharni; Liz Yanti Andriyani; Nurlailah Nurlailah (Jurnal Multidisiplin West Science, 2026)
This study aims to analyze the effect of botanical pesticide use on pest infestation rates in Indonesia using a quantitative approach. Data were collected from 65 respondents involved in agricultural activities through a structured questionnaire based on a Likert scale. The study focuses on measuring respondents’ perceptions regarding the use, effectiveness, and environmental impact of botanical pesticides, as well as the level of pest infestation experienced. Data analysis was conducted using SPSS Version 25, including descriptive statistics, validity and reliability tests, and simple linear regression analysis. The results indicate that botanical pesticide use has a significant negative effect on pest infestation rates, with a regression coefficient of -0.278 and a significance value of 0.003 (< 0.05). This finding suggests that increased use of botanical pesticides contributes to a reduction in pest infestation levels. The coefficient of determination (R²) of 0.135 indicates that 13.5% of the variation in pest infestation rates can be explained by botanical pesticide use, while the remaining variation is influenced by other factors. In conclusion, botanical pesticides are an effective and environmentally friendly alternative for pest management in Indonesia, although their impact is moderate and should be integrated with other pest control strategies. This study contributes to the development of sustainable agriculture by providing empirical evidence on the role of botanical pesticides in reducing pest infestation rates.